DETERMINING POVERTY ALLEVIATION AND SUPPLY CHAIN STRATEGY THROUGH INCREASING ABSORPTION CAPACITY OF VILLAGE BUDGET ALLOCATION - Sufitrayati, Sufitrayati; Nailufar, Fanny; Aliasud, Aliasud; Zulham, T. (International Journal of Supply Chain Management, 2020)
Abstract- This study was aimed to determine poverty alleviation strategy through increasing absorption capacity of Village Budget Allocation (ADG) in underdeveloped villages in Aceh Besar district by supply chain strategy. This research used qualitative descriptive analysis method. The research data consisted of primary data by interviewing the respondents such as community and village apparatus and using pre-prepared questionnaires and secondary data sourced from Central Bureau of Statistics (BPS) [1] and several institutions in Aceh Besar district. The result of the research showed that the provision of Village Budget Allocation in Aceh Besar District has been established in Aceh Besar Regent Regulation issued every year. The amount of ADG is calculated based on the gampong weight value using a certain formula, with the main variables including the number of village apparatus, the number of tuha peut (village supervisor), the number of orphans and the acquisition of poor family rice and other additional variables. Therefore, the use of ADG in Aceh Besar is mostly disbursed to the village apparatus or it is usually called the wages in the form of fixed income, allowances and operational activities of other village [2,3]. Only a small portion was used for orphans' assistance and distribution costs of pre-prosperous family rice. This caused that the benefits of using ADG cannot be perceived by the entire village community. Therefore, the strategy that must be done by the local government of Aceh Besar Regency is to arrange the Regulation of the Regent of Aceh Besar regarding the use of ADG with the rules that are more flexible and not standard so that the use of ADG can give benefit to the whole community of village. Determining the use of ADG should not only be allocated to the village apparatus. The community also had the right to utilize ADG funds together, so as to encourage and provide opportunities for the community to utilize ADG for the needs of the village community. With proper use of targeted ADG, it was expected to reduce poverty levels in village.